Роль жіноцтва в музичній культурі Волині 20–30-х років XX ст. - Никитюк, Н. (Студії мистецтвознавчі, 2008)
The topic of the historic role of women’s society in socio-cultural life of Volyn region of 20–30th of XX century is a milestone that appears at the article due to the complex unification of the principals of cultural and source research. At the same time the regional aspect crossroads with the main direction towards modern gender humanitarian dispute. A number of contemporary historic facts are introduced, different levels of music-socio infrustructure are analized on the objective scientific area. The attention is also drawn to leading Ukrainian Bandura performer of the XX century Hanna Bilohub and active player of the political and cultural movement, first womansenator (Ukrainian representative of Volyn region in Polish senat) Olena Levchanivska.